Photobiomodulation regulates astrocyte activity and ameliorates scopolamine-induced cognitive behavioral decline - Park, Ji On; Hong, Namgue; Lee, Min Young; Ahn, Jin-Chul (Frontiers in Cellular Neuroscience, 2024)
The pathophysiological mechanism of Alzheimer's disease (AD) has not been clearly identified, and effective treatment methods have not yet been established. Scopolamine causes cholinergic dysfunction in the brain, including the accumulation of amyloid-beta plaques, thereby increasing oxidative stress and neuroinflammation, mimicking AD. Glial cells such as astrocytes have recently been identified as possible biomarkers for AD. Photobiomodulation (PBM) elicits a beneficial biological response in cells and tissues. PBM effects on the central nervous system (CNS) have been widely researched, including effects on astrocyte activity. In the present study, PBM was performed using light at the near-infrared wavelength of 825 nm. The Morris water maze and Y-maze tests were employed to evaluate cognitive function decline in a scopolamine-induced memory dysfunction model and its improvement with PBM. In addition, alteration of the mitogen-activated protein kinase (MAPK) pathway and immunofluorescence expression levels of active astrocytes were observed in the hippocampus, which is one of the areas affected by AD, to evaluate the mechanism of action of PBM. A reduction in the neuronal cell death in the hippocampus caused by scopolamine was observed with PBM. Moreover, alteration of a MAPK pathway-related marker and changes in glial fibrillary acidic protein (an active astrocyte marker) expression were observed in the PBM-treated group.Finally, significant correlations between functional and histological results were found, validating the results. These findings indicate the possibility of behavioral and histological improvement due to PBM in scopolamine-induced CNS alteration, which mimics AD. This improvement could be related to neuroinflammatory modulation and altered astrocyte activity.